Improvement of Lamb Preweaning Performance by Combination of Superovulation of Ewes Prior to Mating and Temulawak Extract Plus Administration During Pregnancy - Andriyanto, Andriyanto; Darulfallah, MD; Arif, R; Nugraha, GM; Winarto, A; Manalu, W (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
Abstract. Superovulation is one of a reproductive technology to improve livestock productivity. The research was conducted to optimize the superovulation technology by combining it with administration of temulawak extract plus during pregnancy. Sixteen ewes were injected prostaglandin hormone at a dose of 10 mg/kg body weight intramuscularly twice, with eleven days interval, to synchronize estrous cycle. On the eleventh day, superovulation was induced by injection of pregnant mare serum gonadotrophin hormone at a dose of 200 IU/ewe intramuscularly. The ewes showing the estrous signs were mated naturally. Temulawak extract plus was administered weekly during pregnancy with a dose of 1 mg/kg body weight. Parameters measured in this study were lambs birth weight and preweaning growth. Superovulation increased average litter size. The result showed that, regardless of litter size, superovulation increased lambs birth weight by 15% as compared to controls and temulawak extract plus groups. Superovulation before mating and temulawak extract plus administration during pregnancy improved lambs growth in the first month and the third month postpartum. Superovulation prior to mating increased lambs birth weight and improved lambs growth performance before weaning. Keywords: superovulation, temulawak extract plus, lambs growth performance, ewes Abstrak. Superovulasi merupakan salah satu teknologi reproduksi untuk meningkatkan produktivitas ternak. Penelitian ini dilakukan untuk mengoptimalkan teknologi superovulasi dengan menggabungkan pemberian ekstrak temulawak plus selama kebuntingan. Enam belas domba disuntik hormon prostaglandin dengan dosis 10 mg/kg bobot badan secara intramuskular sebanyak dua kali, dengan selang waktu sebelas hari, untuk menyesuaikan siklus estrus. Pada hari ke sebelas, superovulasi diinduksi dengan injeksi pregnant mare serum gonadotrophin hormon dengan dosis 200 IU/domba secara intramuskuler. Domba yang menunjukkan tanda-tanda estrus kemudian dikawinkan secara alami. Ekstrak temulawak plus diberikan setiap minggu selama kebuntingan dengan dosis 1 mg/kg bobot badan. Parameter yang diukur dalam penelitian ini adalah bobot lahir anak domba dan pertumbuhan prasapih. Superovulasi meningkatkan rata-rata litter size. Hasil penelitian menunjukkan bahwa, terlepas dari litter size, superovulasi meningkatkan bobot lahir anak domba sebesar 15% dibandingkan dengan kelompok ekstrak temulawak plus. Superovulasi sebelum kawin dan pemberian ekstrak temulawak plus selama kebuntingan meningkatkan pertumbuhan anak domba di bulan pertama dan bulan ketiga paska melahirkan. Superovulasi sebelum perkawinan meningkatan berat lahir anak domba dan meningkatan performa pertumbuhan anak domba sebelum penyapihan. Kata kunci: superovulasi, temulawak ekstrak plus, kinerja pertumbuhan anak domba, domba Andriyanto et al/Animal Production 14(3):167-172, September 2012